Proof of Concept Trial of Dronabinol in Obstructive Sleep Apnea - Prasad, Bharati; Radulovacki, Miodrag G.; Carley, David W. (Frontiers in Psychiatry, 2013)
Study Objective: Animal data suggest that ∆9-TetraHydroCannabinol (∆9THC) stabilizes autonomic output during sleep, reduces spontaneous sleep-disordered breathing and blocks serotonin-induced exacerbation of sleep apnea. On this basis, we examined the safety, tolerability, and efficacy of dronabinol (∆9THC), an exogenous Cannabinoid type 1 and type 2 (CB1 and CB2) receptor agonist in patients with Obstructive Sleep Apnea (OSA). Design and Setting: Proof of concept; single-center dose escalation study of dronabinol. Participants: 17 adults with a baseline Apnea Hypopnea Index (AHI) ≥ 15/hour. Baseline polysomnography (PSG) was performed after a 7-day washout of Continuous Positive Airway Pressure (CPAP) treatment. Intervention: Dronabinol was administered after baseline PSG, starting at 2.5 mg once daily. The dose was increased weekly, as tolerated, to 5 mg and finally to 10 mg once daily. Measurements and Results: Repeat PSG assessments were performed on nights 7, 14, and 21 of dronabinol treatment. Change in AHI (∆AHI, mean ± Standard Deviation; SD) was significant from baseline to night 21 (-14.1 ±17.5; p= 0.007). No degradation of sleep architecture or serious adverse events was noted. Conclusions: Dronabinol treatment is safe and well-tolerated in OSA patients at doses of 2.5 mg to 10 mg daily and significantly reduces AHI in the short-term. These findings should be confirmed in a larger study in order to identify sub-populations with OSA that may benefit from cannabimimetic pharmacologic therapy.